2018
DOI: 10.31327/jee.v3i2.853
|View full text |Cite
|
Sign up to set email alerts
|

Listening Material in the 2013 Curriculum English Textbook: What Do the Teachers Think?

Abstract: Listening is considered as the basic skill in learning a language.  Listening lets students gain input in the form of audio. Due to the 2013 curriculum, schools are provided with English textbook prepared by the government. This textbook is used for the listening input which may affect the output of listening process. Therefore, the researchers are interested in conducting a research related to the weaknesses of the K13 English textbook When English Rings a Bell. The researchers want to know the weaknesses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(5 reference statements)
1
7
0
Order By: Relevance
“…Qodriani [3] said in the electronic school book "English Junior High School/MTs 2013 Curriculum When English Rings the Bell" showed that there are no written pronunciation learning activities, no summary rules for using grammar, and no maximum use of teaching aids (tapes, recordings, videos, etc.). This result is confirmed by Oktalia et al [4] in their research. It found various flaws in the "K13 English textbook When English Rings a Bell," and those have an impact on language learning output.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Qodriani [3] said in the electronic school book "English Junior High School/MTs 2013 Curriculum When English Rings the Bell" showed that there are no written pronunciation learning activities, no summary rules for using grammar, and no maximum use of teaching aids (tapes, recordings, videos, etc.). This result is confirmed by Oktalia et al [4] in their research. It found various flaws in the "K13 English textbook When English Rings a Bell," and those have an impact on language learning output.…”
Section: Introductionsupporting
confidence: 85%
“…Oktalia et al [4] also conducted research into teachers' perceptions of the textbook, titled Listening material in the 2013 curriculum English textbook: What do the teachers think? This research tries to discover the flaws in the textbook's listening material, as determined by the teachers' perceptions.…”
Section: Previous Related Researchesmentioning
confidence: 99%
“…Even though it is simple to obtain auditory materials, there is no assurance that each will meet the requirements or learning objectives of the students. Text-to-speech software as an instrument for the production of listening materials is one possible solution (Oktalia and Drajati 2018). Even if listening resources are simple to obtain, there is no assurance that each one will satisfy the needs of the students or the learning purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Google Sites serves as a platform for students to collaborate and discuss lesson concerns or share ideas within their groups (Ma et al, 2018). Through this platform, teachers or peers can support learning by offering more immediate and frequent feedback (Oktalia & Drajati, 2018). Additionally, learning is made more contextualized as teachers can use various teaching materials like videos and animations to connect the subject matter to real-world situations.…”
Section: Introductionmentioning
confidence: 99%